2009
DOI: 10.1016/j.crte.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The fresh water-seawater contact in coastal aquifers supporting intensive pumped seawater extractions: A case study

Abstract: The construction of desalination plants along the Mediterranean coast that are supplied with seawater via pumped boreholes in coastal aquifers has given rise to novel hydrogeological situations. At the experimental site on the Andarax delta (SE Spain), a monitoring system has been set up, consisting of piezometer clusters. Piezometric level and electrical conductivity are monitored continuously at various depths in the aquifer. The data obtained allow the response of the aquifer to the intensive saltwater extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Moving to field-based monitoring strategies where a direct acquisition of GW samples in the field is planned, was can see that in the vast majority of cases, the acquisition of the GW sample is carried out in pre-existing wells, which were not explicitly designed for research purposes, and by means of standard integrated depth sampling (IDS). On the other hand, the studies carried out via dedicated multi-level samplers (MLSs) to determine the heads and groundwater quality variations induced by saltwater intrusion [52] or to quantify the salinization impact of pumping wells used to feed desalination plants [53] are far less numerous. In all the cases, the use of MLSs enabled the clear recognition of the transition zone variations due to change in vertical shift of the fresh-saline interface and to clearly identify the different sources of salinity that could be present in coastal environments and that are hardly identifiable by using standard integrated depth borehole data [54,55].…”
Section: Methodological Approaches For Groundwater Salinization Delinmentioning
confidence: 99%
“…Moving to field-based monitoring strategies where a direct acquisition of GW samples in the field is planned, was can see that in the vast majority of cases, the acquisition of the GW sample is carried out in pre-existing wells, which were not explicitly designed for research purposes, and by means of standard integrated depth sampling (IDS). On the other hand, the studies carried out via dedicated multi-level samplers (MLSs) to determine the heads and groundwater quality variations induced by saltwater intrusion [52] or to quantify the salinization impact of pumping wells used to feed desalination plants [53] are far less numerous. In all the cases, the use of MLSs enabled the clear recognition of the transition zone variations due to change in vertical shift of the fresh-saline interface and to clearly identify the different sources of salinity that could be present in coastal environments and that are hardly identifiable by using standard integrated depth borehole data [54,55].…”
Section: Methodological Approaches For Groundwater Salinization Delinmentioning
confidence: 99%
“…Two seawater desalination plants have been commissioned in the area to provide a new water source that will enable the continuation of urban and agricultural development. They are situated in the Andarax delta and close to the coast near Cabo de Gata (Figure 3a); both are supplied with seawater taken from coastal boreholes (Gühl et al , 2006; Jorreto et al , 2009; Rodríguez‐Estrella and Pulido‐Bosch, 2009).…”
Section: Geological and Hydrogeological Frameworkmentioning
confidence: 99%
“…23 By pumping SGW, FSI is pushed deeper and toward the sea. 24,25 In addition, water analyses showed that the groundwater is filtered while flowing through the sediment, which reduces the amount of particles (SDI) by more than 90%. 15,26 The purpose of this study was to examine the suitability of SGW as feedwater for RO desalination by characterizing the chemical, physical and biological properties of the saline groundwater and of seawater, and by evaluating the performance, efficiency and fouling propensity of RO desalination of the two water types.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One example is the facility in Sur, Oman, which is the largest desalination facility that uses SGW as feed with permeate productivity of 60 MCMY . By pumping SGW, FSI is pushed deeper and toward the sea. , In addition, water analyses showed that the groundwater is filtered while flowing through the sediment, which reduces the amount of particles (SDI) by more than 90%. , …”
Section: Introductionmentioning
confidence: 99%